Health informatics in Sweden – a personal view - Koch, Sabine (International journal on biomedicine and healthcare, 2017)
This paper summarizes my health informatics journey starting as an undergraduate student in medical informatics in 1988 until my current position at Karolinska Institutet in Stockholm where I was appointed as the first full professor in health informatics in 2008. Besides my own and my group's work in the fields of dental informatics, collaborative home care, clinical informatics and consumer informatics, this paper further gives an overview of health informatics research, education and implementation in Sweden. My personal view on the future of this exciting crossdisciplinary field concludes this paper.
Keywords: Health Information Exchange; informatika v zubním lékařství; Sweden; telemedicína; portál pacienta; Patient Portals; lékařská informatika; Telemedicine; výměna zdravotnických informací; Medical Informatics; Švédsko; Dental Informatics